2003
DOI: 10.1046/j.1468-1331.2003.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II genotypes in Mexican Mestizo patients with myasthenia gravis

Abstract: Myasthenia gravis is an autoimmune, heterogeneous disorder, characterized by the presence of antibodies against acetylcholine receptors at the neuromuscular junction. There is a strong evidence that an individual's genetic composition is an important predisposing factor for the development of the disease. To correlate HLA class II genotypes with thymic pathology in Mexican Mestizo patients who had been subjected to thymectomy. HLA class II genes were analyzed in 60 patients and in 99 healthy ethnically matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
(22 reference statements)
1
9
1
2
Order By: Relevance
“…Barton et al found that there was a statistically significant negative association between MG and HLA-DR2 in Jamaicans, 16 and García-Ramos et al found that DR4 is a protective allele for Mexican Mestizo patients with MG with thymoma. 17 In our study, we found a lower prevalence of the HLA-DRB1 ⁄ 08 allele among patients with MG, especially in the early-onset group and the AChR seropositive group. HLA-DRB1 ⁄ 08 may be a protective allele for these groups of MG; however, more studies are necessary to better understand the relationship.…”
Section: Discussionsupporting
confidence: 51%
“…Barton et al found that there was a statistically significant negative association between MG and HLA-DR2 in Jamaicans, 16 and García-Ramos et al found that DR4 is a protective allele for Mexican Mestizo patients with MG with thymoma. 17 In our study, we found a lower prevalence of the HLA-DRB1 ⁄ 08 allele among patients with MG, especially in the early-onset group and the AChR seropositive group. HLA-DRB1 ⁄ 08 may be a protective allele for these groups of MG; however, more studies are necessary to better understand the relationship.…”
Section: Discussionsupporting
confidence: 51%
“…A Mexican is usually considered as a mestizo, defined as an individual who was born in Mexico and is a descendant from the native inhabitants of such region, and from individuals, mainly from Spain or from Africa, who came to America during the 16th century (35). Mexican mestizo individuals have a proportion of 56% Native American Indian genes, 40% Caucasian genes, and 4% African genes (36).…”
Section: Methodsmentioning
confidence: 99%
“…This racial category may vary from having very dominant white characteristics to very dominant Native American characteristics. 25 28 Other risk factors, currently known or unknown, might also influence the performance of existing osteoporosis risk tools in Latin America. Considering these factors, a risk assessment tool specifically developed for Latin American populations might be most appropriate.…”
mentioning
confidence: 99%